Cellular and molecular mechanisms regulating neuronal growth by brain‐derived neurotrophic factor. Issue 10 (13th June 2016) - Gonzalez, Andres; Moya‐Alvarado, Guillermo; Gonzalez‐Billaut, Christian; Bronfman, Francisca C.
Abstract : Brain‐derived neurotrophic factor (BDNF) and its receptors TrkB and p75 regulate dendritic and axonal growth during development and maintenance of the mature nervous system; however, the cellular and molecular mechanisms underlying this process are not fully understood. In recent years, several advances have shed new light on the processes behind the regulation of BDNF‐mediated structural plasticity including control of neuronal transcription, local translation of proteins, and regulation of cytoskeleton and membrane dynamics. In this review, we summarize recent advances in the field of BDNF signaling in neurons to induce neuronal growth. © 2016 Wiley Periodicals, Inc.